2019
DOI: 10.1039/c8sm02006j
|View full text |Cite
|
Sign up to set email alerts
|

Infinite coordination polymer networks: metallogelation of aminopyridine conjugates and in situ silver nanoparticle formation

Abstract: Self-assembly of silver(i) and low molecular weight organic ligands derived from aminopyridine conjugates led to in situ generation of an infinite coordination polymer network and ultra small nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…The microscopic changes occurring in molecular gels are attributed to noncovalent intermolecular interactions responsible for the molecular self-assembly. The noncovalent interactions such as hydrogen bonding, electrostatic effect, hydrophobic effect, London dispersion forces, van der Waals interactions, charge-transfer complexation, metal coordination, halogen bonding, and fluorine–fluorine interactions , have been explored effectively for designing new gelators. Extensive research, pursued over the last three decades on diverse building blocks, has offered the possibilities toward the rational design of molecular gelators with unique material properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microscopic changes occurring in molecular gels are attributed to noncovalent intermolecular interactions responsible for the molecular self-assembly. The noncovalent interactions such as hydrogen bonding, electrostatic effect, hydrophobic effect, London dispersion forces, van der Waals interactions, charge-transfer complexation, metal coordination, halogen bonding, and fluorine–fluorine interactions , have been explored effectively for designing new gelators. Extensive research, pursued over the last three decades on diverse building blocks, has offered the possibilities toward the rational design of molecular gelators with unique material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research, pursued over the last three decades on diverse building blocks, has offered the possibilities toward the rational design of molecular gelators with unique material properties. The building blocks ranging from long chain hydrocarbons, peptides, polyaromatics, steroids, carbohydrates, and metal complexes have been studied extensively. Molecular gels are generally considered as kinetically trapped metastable states, and the gelation process can be controlled by tuning the supramolecular interactions and self-assembly pathways to obtain different material properties. , It has been shown that there is a delicate balance between gelation and crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Furthermore, certain metal ions also serve as a source for in situ metal nanoparticle formation. [19][20][21][22] Therefore, metallogels find potential applications in chiral recognition, light-emitting materials, soft conductive materials, wearable electronics, energy storage, selfhealing devices, catalysis, and antimicrobial systems, and can act as artificial enzyme mimics. [23][24][25][26][27] Metallogels contain metal components and organic components with appropriate binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Metallogels involving low molecular weight organic ligands result in discrete coordination complexes or coordination polymerization upon complexation. [19][20][21][22] When the gelation consists of the selfassembly of discrete complexes, the supramolecular interactions between the organic ligands act as the primary driving force, whereas, for coordination polymerization-induced gelation, the metal-ligand interaction forms the main driving force. 35,36 For supramolecular metallogels, the gelation can be induced by adding metal salt into a solution containing organic ligands with appropriate binding sites or by dissolving a premade metal complex.…”
Section: Introductionmentioning
confidence: 99%
“…The building blocks of hierarchical gels comprise a wide variety of compounds, namely long chain hydrocarbons, [25] peptides, [15b] polyaromatics, [26] steroids, [27] carbohydrates, [28] metal complexes [29] and amino acid‐derived surfactants [30] . Gels built of tubular aggregates, like nanofibers and nano/microtubes, have some advantages over other soft materials, namely the high surface area, high surface energy and enhanced entrapping efficiency compared with bulk materials [3a, 12] .…”
Section: Introductionmentioning
confidence: 99%